Challenge-based learning and design thinking in higher education: institutional strategies for linking experiential learning, innovation, and academic performance (2024)
This research describes the results of the implementation of the Challenge Based Learning (CBL) with the Design Thinking (DT) methodology, evaluating its stages for the co-creation of solutions to challenges in business contexts combined with an innovative institutional strategy in the higher education. This methodology, articulated with the CBL strategy at the Universidad de la Costa Barranquilla Colombia, facilitates the technological development, research and innovation products, achieving learning results and generic competencies stipulated in the subjects, regardless of the profession the student is pursuing. The results show the concentration of pedagogical and didactic strategies due to their effectiveness in achieving the learning results of the subjects, obtaining the solution to the challenge and associated products. Finally, the test results of students’ generic competencies improve by 55% when compared to previous periods where the strategy was not executed, contributing with products that have a favourable impact on the social environment.